INVESTIGATING MINERALOGICAL AND PHYSIO-CHEMICAL PROPERTIES OF BENTONITE FOR WATER-BASED FLUIDS - Masoomeh Bakhshi; Mohammad-Reza Mozdianfard; Majid Hayati-Ashtiani (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2020)
Bentonite is a well-known type of clay and the mineralogical and physio-chemical characterization of its suspensions is essential to be investigated. In this study, the mineralogical and Physio-chemical characterization of the nano-porous structure of four industrial-grade bentonite samples namely, B1, B2, B3 and B4 were investigated to determine their mineralogical properties for a specific industrial application. Instrumental analyses of samples using XRD, XRF and BET were investigated along with laboratory tests including swelling and sediment indices, surface area and cation exchange capacity as well in order to select the appropriate sample. XRF along with slurry pH shows alkali metal ions. The results indicate B4 has calcite impurity, 50 cP viscosity reading at 600 r/min, 6 value for yield point/plastic viscosity ratio and 39.05 wt% residue of diameter greater than 75 μm. B3 is the most suitable sample for water-based fluid utilization compared to B1, B2 and B4, which satisfies the best standard requirements.